LAS METAMORFOSIS DE OVIDIO SEGÚN RAPHAEL REGIUS: ALGUNOS EJEMPLOS - Rosa María Iglesias Montiel; Mª Consuelo Álvarez Morán (Exemplaria Classica, 2016)
This paper analyses some passages from Raphael Regius’ commentary on Ovid’s Metamorphoses, in which the humanist provides suggestions and textual emenda- tions. Many of his contributions have been accepted or discussed by the scholars all over the last centuries.